THE PROBLEM OF THE RELATIONSHIP OF PHRASEOLOGISMS AND PROVERBS IN THE LANGUAGE - Toshtemirov, Elyor (Educational Research in Universal Sciences, 2023)
The article describes problems concerning the relationship of phraselogisms and proverbs in the language. As long as phraseologisms and proverbs are the wealth of the language, they have useful feature in expressing ideas effectively, it is natural to use them effectively in speech and language.